If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 26 = 3x + 20 Reorder the terms: 26 + 9x = 3x + 20 Reorder the terms: 26 + 9x = 20 + 3x Solving 26 + 9x = 20 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 26 + 9x + -3x = 20 + 3x + -3x Combine like terms: 9x + -3x = 6x 26 + 6x = 20 + 3x + -3x Combine like terms: 3x + -3x = 0 26 + 6x = 20 + 0 26 + 6x = 20 Add '-26' to each side of the equation. 26 + -26 + 6x = 20 + -26 Combine like terms: 26 + -26 = 0 0 + 6x = 20 + -26 6x = 20 + -26 Combine like terms: 20 + -26 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| 4x-3x^3=0 | | 3y+y=72 | | 5x-3x=3+4x | | y=8-x^2-2x | | 8/3:x=4/5:3 | | x+75=2x-20 | | (4+1)*3= | | (2+4)*1= | | 9-3*1= | | N+7n-2=22 | | 2a+2b=86 | | 3-8/4= | | Log(x)+2-2x=0 | | 6/2*3 | | 5+7*6= | | 30r^2-30r=0 | | 6/2x4 | | Ln(x)+2-2x=0 | | x^3-10*x^2+19*x+30=0 | | x^4-10*x^3+19*x^2+30*x=0 | | 2x-4(14x-6)=0 | | (x-6)2=188 | | 2x-12-2x-12-y-y=360 | | y^3-8y^3/2=64 | | 4y-(6*(-3)+6y*(-3))=26 | | 6(1+2)-4y= | | 2cosx-sin^2x-1=0 | | (7x+2)-(4x-9)= | | y=4x+10-2 | | y=x^3-9x^2+15x | | 3y+0.5x=3 | | 2*sinx*cosx= |